Studies in Manichaean Literature and Art - Heuser, Manfred, (Nag Hammadi and Manichaean Studies ;, 1998)
This volume consists of two sections, written by the two authors. The first section contains a study by Manfred Heuser on The Manichaean Myth According to Coptic Sources . This is the first systematic presentation of the basic myth as reflected in Coptic material. The second part is a collection of essays on Manichaeism by Hans-Joachim Klimkeit. The essays are concerned, inter alia, with Manichaean art and symbolism, including newly found examples of Manichaean art from Central Asia.